Sapientia Salomonis = (Weisheit Salomos) - Niebuhr, Karl-Wilhelm; Nesselrath, Heinz-Günther, 1957-; Nesselrath, Heinz-Günther, 1957- (Sapere (Darmstadt, Germany) ;, 2015)
Text of the Wisdom of Solomon in the original Greek, with German translation on facing pages. Detailed introduction, commentary, and critical essays in German.